Removal of hydrogen chloride from flue gases with calcined limestone particles in a fixed bed reactor - Akosman, C; Walters, JK (Parlar Scientific Publications (P S P), 2003)
The sorption of hydrogen chloride gas (HCl) on fully calcined commercial limestone particles was experimentally investigated using a fixed bed reactor at temperatures between 400-650 degreesC. The gas phase was a mixture of HCl and N-2 with an inlet HCl concentration of 0.5% mol. The limestone particles were diluted in inert mullite beads to obtain a proper gas-solid contact. The experimental results showed that the conversion of solids increased with increasing temperature. Also HCl removal efficiency increased with increase in temperature and limestone quantity in the bed.
Keywords: HCl removal; fixed bed; gas cleaning; limestone utilisation